2016
DOI: 10.1536/ihj.16-049
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Neutrophil-to-Lymphocyte Ratio in Predicting Adverse Events in Elderly Patients With Chronic Heart Failure

Abstract: SummaryThe neutrophil-to-lymphocyte (N/L) ratio has been associated with poor outcomes in patients with cardiovascular diseases, but it has not been studied in elderly patients with chronic heart failure (CHF).In this study, we analyzed 1355 elderly patients admitted with CHF. A multivariate logistic regression model was used to assess the independent association of the N/L ratio with chronic kidney disease (CKD). The patients were then divided into tertiles according to the N/L ratios. We used Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
(33 reference statements)
1
27
1
Order By: Relevance
“…In elderly patients with CHF, NLR was independently correlated with the occurrence of major cardiovascular events (MCE), as well as with CKD [34]. During a median follow-up period of 18 months, those with the highest tertile of the NLR (median 4.1, interquartile range 3.39 to 6.01) had a significantly higher incidence of cardiac death and rehospitalization for heart failure [34].…”
Section: Heart Failure In Elderly Patientsmentioning
confidence: 99%
“…In elderly patients with CHF, NLR was independently correlated with the occurrence of major cardiovascular events (MCE), as well as with CKD [34]. During a median follow-up period of 18 months, those with the highest tertile of the NLR (median 4.1, interquartile range 3.39 to 6.01) had a significantly higher incidence of cardiac death and rehospitalization for heart failure [34].…”
Section: Heart Failure In Elderly Patientsmentioning
confidence: 99%
“…It is now established that certain molecules combined chronic inflammatory process and underlying endothelial dysfunction play important role in development of insulin resistance, diabetes and associated complications [12,13]. Neutrophilia or lymphopeniais associated with high NLR while lymphocytosis or neutropenia with low NLR [14]. Literature suggest that neutrophilia and relative lymphocytopeniaare independent markers for diabetic neuropathy including neuropathy [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…NLR is not affected by the acute inflammation of the whole body; unlike the absolute value of simple neutrophils, it is a more stable indicator of systemic inflammation and a prognostic marker in patients with cancer, coronary artery disease, heat failure, TIA, and calcification aortic valve disease. [29][30][31] The NLR is more stable than the pure white blood cell count, which is not easily disturbed by the other factors in the blood samples, and has a more predictive value. In 2013, Bilen, et al found that BAV is associated with elevated mean platelet volume (MPV).…”
Section: Discussionmentioning
confidence: 99%